High-thermal-conductivity distributed copper-aluminum composite current collector
Patent Information
- Application Number
- CN202311029532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-16
AI Technical Summary
不管是铜箔还是铝箔,都是单体材料,其表面只能涂覆单一活性物质正极材料或者负极材料,但刚性金属集流体与活性材料颗粒见的接触面积有限,不仅限制了锂电池的结构设计多样性,同时还会造成界面电阻变大,引起内阻上升,容易发生着火或爆炸
[0022]与现有技术相比,本发明所达到的有益效果是:本发明制备了一种高导热分布式铜铝复合集流体,有效减少了电池内部应力的影响,避免极片出现褶皱,同时解决了极耳在叠片过程中易断的问题,集流体的穿测强度大于100gf,水平和垂直拉伸强度均大于100MPa,水平和垂直延伸率大于2%。
Smart Images

Figure CN117080452B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a high thermal conductivity distributed copper-aluminum composite current collector. Background Technology
[0002] Current collectors are an indispensable component of lithium-ion batteries. Current current collector manufacturing processes typically use pure copper foil as the negative electrode and pure aluminum foil as the positive electrode. Active slurry is directly coated onto the surfaces of the copper and aluminum foil current collectors. Pure aluminum foil is prepared using a rolling process, while pure copper foil is prepared using an electrolytic process. However, both copper and aluminum foils are single-electrode materials, meaning their surfaces can only be coated with a single active material (positive or negative electrode). The limited contact area between the rigid metal current collector and the active material particles not only restricts the diversity of lithium-ion battery structural designs but also increases interfacial resistance, leading to increased internal resistance and a higher risk of fire or explosion. Therefore, it is necessary to develop a highly thermally conductive adhesive layer that can not only improve the adhesion between the film and the electrode but also quickly dissipate heat generated inside the battery, preventing fires. Summary of the Invention
[0003] The purpose of this invention is to provide a high thermal conductivity distributed copper-aluminum composite current collector to solve the problems mentioned in the background art.
[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0005] Step 1:
[0006] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, and obtain polyvinyl alcohol solution; mix acrylamide, acrylic acid, and water and dissolve by ultrasonication to obtain material A; mix acrolein, acrylic acid, sodium 2-acrylamide-2-methylpropanesulfonate, ferric chloride, pyrrole, and water, and stir to react for 2-3 hours to obtain material B;
[0007] S2: Under nitrogen atmosphere, add material A and potassium persulfate to polyvinyl alcohol solution, heat to 40-60℃, and react for 4-6 hours; add material B in 3-6 portions and continue the reaction for 6-8 hours; add ammonia water to adjust pH to 7-7.5 to obtain adhesive emulsion.
[0008] S3: Disperse silicon carbide powder in water, add polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder;
[0009] Step 2: Mix modified silicon carbide powder, nano silver powder and binder emulsion by weight percentage, stir for 30-60 minutes to obtain a high thermal conductivity adhesive coating liquid, unwind the polymer film and coat it on the upper and lower surfaces to form a high thermal conductivity adhesive layer.
[0010] Step 3: Take aluminum sheet and copper sheet, roll the aluminum sheet into aluminum foil; roll the copper sheet into copper foil; combine the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, heat age and roll up to obtain a high thermal conductivity distributed copper-aluminum composite current collector.
[0011] Furthermore, in S1, the content of each component in the polyvinyl alcohol solution, by weight percentage, is 15-20% polyvinyl alcohol and 80-85% deionized water.
[0012] Furthermore, in S1, the content of each component of material A, by weight percentage, is 30-40% acrylamide, 10-20% acrylic acid, and 40-60% water.
[0013] Furthermore, in S1, the content of each component of material B, by weight percentage, is: 10-15% acrolein, 35-45% acrylic acid, 5-10% sodium 2-acrylamide-2-methylpropanesulfonate, 10-15% ferric chloride, 2-3% pyrrole, and the remainder is water.
[0014] Furthermore, in S2, the amounts of each component in the adhesive emulsion, by weight, are: 3.2–4.8 parts polyvinyl alcohol solution, 1.6–2.4 parts material A, 0.05–0.08 parts potassium persulfate, and 4.4–5.6 parts material B.
[0015] Furthermore, in S3, the amounts of each component, by weight, are 15-20 parts silicon carbide powder, 100 parts water, and 22-28 parts polyethyleneimine.
[0016] Furthermore, in step 2, the content of each component in the high thermal conductivity adhesive coating liquid, by weight percentage, is 15-20% modified silicon carbide powder, 0.3-0.5% nano silver powder, and 75-80% adhesive emulsion.
[0017] Furthermore, in step 2, the unwinding tension is 50–200 N.
[0018] Furthermore, in step 2, the surface density of the high thermal conductivity adhesive coating liquid on one side is 1–20 g / m². 2 .
[0019] Furthermore, in step 3, the aluminum foil thickness is 5–20 μm and the copper foil thickness is 2–15 μm.
[0020] Furthermore, in step 3, the composite pressure is 0.5–1.5 MPa, the composite temperature is 30–40 °C, the composite speed is 100–200 m / min, the thermal aging temperature is 30–50 °C, the time is 5–50 s, and the winding tension is 50–200 N.
[0021] Furthermore, in step 3, the thickness of the copper-aluminum composite current collector is 10–70 μm.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: The present invention prepares a high thermal conductivity distributed copper-aluminum composite current collector, which effectively reduces the influence of internal stress in the battery, avoids wrinkles in the electrode, and solves the problem of easy breakage of the electrode tab during the stacking process. The current collector has a penetration strength greater than 100gf, a horizontal and vertical tensile strength greater than 100MPa, and a horizontal and vertical elongation greater than 2%.
[0023] In this invention, a high thermal conductivity adhesive layer is formed on the surface of a polymer film by preparing a high thermal conductivity adhesive layer coating liquid, which can promptly dissipate heat generated inside the battery and prevent battery fire. In preparing the high thermal conductivity adhesive layer coating liquid, acrylamide, acrylic acid, and water are mixed to obtain component A; acrolein, acrylic acid, sodium 2-acrylamide-2-methylpropanesulfonate, ferric chloride, and pyrrole are mixed and reacted to obtain component B; component A is first mixed with polyvinyl alcohol and polymerized under the action of potassium persulfate, introducing acrylic acid and acrylamide onto the side chains of polyvinyl alcohol. After the polymerization reaction has proceeded for 4-6 hours, component B is added to continue the reaction. In component B, sodium 2-acrylamide-2-methylpropanesulfonate facilitates the stable dispersion of polymer molecules in the emulsion and also improves the heat resistance of the adhesive layer coating liquid; acrolein, through its aldehyde group, can react with pyrrole to generate an imine, thereby grafting the conductive polymer polypyrrole onto the emulsion through chemical bonds.
[0024] When preparing a high thermal conductivity adhesive coating, controlling the amount of acrylic acid in component B to 35-45% provides an acidic environment for pyrrole self-polymerization and the reaction of pyrrole with acrolein, eliminating the need to introduce other inorganic or organic acids. Acrylic acid also participates in the polymerization, improving the viscosity of the high thermal conductivity adhesive coating. Simultaneously, component A is reacted with polyvinyl alcohol for a period of time before adding component B. This is because if component B is directly blended with component A, on the one hand, component A and polyvinyl alcohol will dilute the acrylic acid in component B, causing a change in the pH value of the reaction system, thus affecting the self-polymerization of pyrrole and its reaction with acrolein; on the other hand, because the acrylic acid content in component B is too high, direct blending with component A will cause a large amount of acrylic acid to self-polymerize in a short time, resulting in an increase in the overall viscosity of the system and affecting the synthesis of the coating. Therefore, reacting component A with polyvinyl alcohol for a period of time first, and then slowly adding component B in 3-6 increments, yields a better product. This method introduces conductive polypyrrole into the coating, thereby improving the conductivity of the coating.
[0025] The present invention also uses polyethyleneimine to modify the thermally conductive silicon carbide material to obtain modified silicon carbide powder. The amino groups on the surface of the modified silicon carbide powder can react with the amide groups on the acrylamide side chain of polyvinyl alcohol, thereby improving the dispersibility of the silicon carbide powder in the coating liquid, and thus the resulting coating has better thermal conductivity. Attached Figure Description
[0026] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:
[0027] Figure 1 This is a schematic diagram of the copper-aluminum composite current collector structure prepared according to the present invention.
[0028] In the figure, 1-copper layer; 2-high thermal conductivity adhesive layer; 3-polymer film; 4-aluminum layer. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] There are no special restrictions on the suppliers of any of the raw materials involved in this invention. Exemplary examples include: the polymer film is a BOPP film purchased from Zhejiang Dasoutheast, with a thickness of 5μm; the silicon carbide powder is purchased from Yishan Polishing Materials, item number FP09991; the polyacrylic acid adhesive is purchased from Sanying New Materials, model SY-302; the polyethyleneimine is purchased from Youen Chemical, model UN-2580; the copper sheet is purchased from Xinyue Metal, item number ZTD2018090T2; and the aluminum sheet is purchased from Flex Insulation Building Materials, item number lp123tt.
[0031] Example 1: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0032] Step 1:
[0033] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0034] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 40 °C, and the reaction was carried out for 4 h; 5.4 kg of material B was added in 4 portions and the reaction was continued for 6 h; ammonia water was added to adjust the pH to 7 to obtain the adhesive emulsion.
[0035] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0036] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 30 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0037] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1MPa, a composite temperature of 35℃, and a composite speed of 100m / min; heat age at 50℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0038] Example 2: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0039] Step 1:
[0040] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0041] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 45℃ and the reaction was carried out for 4 h; 5.4 kg of material B was added in 4 portions and the reaction was continued for 6.5 h; ammonia water was added to adjust the pH to 7.2 to obtain the adhesive emulsion.
[0042] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0043] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 40 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0044] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 0.8MPa, a composite temperature of 35℃, and a composite speed of 100m / min; heat age at 40℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0045] Example 3: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0046] Step 1:
[0047] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0048] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 50 °C, and the reaction was carried out for 5 h; 5.4 kg of material B was added in 4 portions and the reaction was continued for 7.5 h; ammonia water was added to adjust the pH to 7.5 to obtain the adhesive emulsion.
[0049] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0050] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 45 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N. Coat the upper and lower surfaces separately, with a single-sided coating density of 10 g / m². 2 This forms a highly thermally conductive adhesive layer;
[0051] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1MPa, a composite temperature of 45℃, and a composite speed of 100m / min; heat age at 35℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0052] Example 4: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0053] Step 1:
[0054] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0055] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 60 °C, and the reaction was carried out for 4 h; 5.4 kg of material B was added in 5 portions and the reaction was continued for 6 h; ammonia water was added to adjust the pH to 7.5 to obtain the adhesive emulsion.
[0056] S3: Disperse 20g of silicon carbide powder in 100g of water, add 25g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder;
[0057] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 30 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0058] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1.1MPa, a composite temperature of 40℃, and a composite speed of 100m / min; heat age at 45℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0059] Example 5: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0060] Step 1:
[0061] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 3 hours to obtain material B;
[0062] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.6 kg of polyvinyl alcohol solution, the temperature was raised to 60 °C, and the reaction was carried out for 5.5 h; 5.4 kg of material B was added in 5 portions and the reaction was continued for 6 h; ammonia water was added to adjust the pH to 7 to obtain the adhesive emulsion.
[0063] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0064] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 55 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0065] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 0.5MPa, a composite temperature of 35℃, and a composite speed of 100m / min; heat age at 45℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0066] Example 6: A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector, comprising the following steps:
[0067] Step 1:
[0068] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 3 hours to obtain material B;
[0069] S2: Under nitrogen atmosphere, 2.4 kg of material A and 0.05 kg of potassium persulfate were added to 4.75 kg of polyvinyl alcohol solution, the temperature was raised to 55 °C, and the reaction was carried out for 4.5 h; 5 kg of material B was added in 6 portions and the reaction was continued for 7 h; ammonia water was added to adjust the pH to 7.5 to obtain the adhesive emulsion.
[0070] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0071] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 55 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0072] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1.5MPa, a composite temperature of 40℃, and a composite speed of 100m / min; heat age at 50℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0073] Comparative Example 1: A copper-aluminum composite current collector was prepared using a conventional polyacrylic acid adhesive, with all other parameters being the same as in Example 1.
[0074] Step 1: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder;
[0075] Step 2: By weight percentage, mix 15% modified silicon carbide powder, 5% nano silver powder, and 80% polyacrylic acid binder, and stir for 30 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0076] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1MPa, a composite temperature of 35℃, and a composite speed of 100m / min; heat age at 50℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0077] Comparative Example 2: Silicon carbide was not modified using polyethyleneimine, and all other parameters were the same as in Example 2.
[0078] Step 1:
[0079] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0080] S2: Under nitrogen atmosphere, 2.1 kg of material A and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 45℃ and the reaction was carried out for 4 h; 5.4 kg of material B was added in 4 portions and the reaction was continued for 6.5 h; ammonia water was added to adjust the pH to 7.2 to obtain the adhesive emulsion.
[0081] Step 2: By weight percentage, mix 19.5% silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 40 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N; coat the upper and lower surfaces respectively, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0082] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 0.8MPa, a composite temperature of 35℃, and a composite speed of 100m / min; heat age at 40℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0083] Comparative Example 3: In S2, components A and B were mixed and reacted with polyvinyl alcohol simultaneously, and the remaining parameters were the same as in Example 3.
[0084] Step 1:
[0085] S1: Disperse polyvinyl alcohol in water, heat and stir to dissolve, to obtain a 20 wt.% polyvinyl alcohol solution; mix 40% acrylamide, 10% acrylic acid, and 50% water by weight percentage, and sonicate to dissolve to obtain material A; mix 15% acrolein, 30% acrylic acid, 7% sodium 2-acrylamide-2-methylpropanesulfonate, 15% ferric chloride, 3% pyrrole, and 30% water by weight percentage, and stir to react for 2 hours to obtain material B;
[0086] S2: Under nitrogen atmosphere, 2.1 kg of material A, 5.4 kg of material B and 0.05 kg of potassium persulfate were added to 4.8 kg of polyvinyl alcohol solution, the temperature was raised to 50 °C, the reaction was carried out for 12.5 h, and ammonia water was added to adjust the pH to 7.5 to obtain the adhesive emulsion.
[0087] S3: Disperse 18g of silicon carbide powder in 100g of water, add 24g of polyethyleneimine, stir evenly, and then spray dry to obtain modified silicon carbide powder.
[0088] Step 2: By weight percentage, mix 19.5% modified silicon carbide powder, 0.5% nano silver powder, and 80% binder emulsion, and stir for 45 minutes to obtain a high thermal conductivity adhesive coating liquid. Unwind the polymer film with an unwinding tension of 80 N. Coat the upper and lower surfaces separately, with a single-sided coating density of 10 g / m². 2 Forms a highly thermally conductive adhesive layer;
[0089] Step 3: Take aluminum and copper sheets, roll the aluminum sheet into an aluminum foil with a thickness of 6μm; roll the copper sheet into a copper foil with a thickness of 6μm; composite the aluminum foil and copper foil with a high thermal conductivity adhesive layer respectively, with a composite pressure of 1MPa, a composite temperature of 45℃, and a composite speed of 100m / min; heat age at 35℃ for 15s, and then wind up to obtain a 20μm copper-aluminum composite current collector with a winding tension of 120N.
[0090] experiment:
[0091] The mechanical properties of the copper-aluminum composite current collectors prepared in Examples 1 to 6 were tested using a tensile testing machine. The test results are shown in Table 1 below.
[0092] Tensile strength: Fix the sample at both ends using a tensile testing machine; start the tensile testing machine, stretch the sample, and record the data when it breaks. This data is the tensile strength.
[0093] Elongation: Fix the sample at both ends using a tensile testing machine; start the tensile testing machine to perform a tensile test on the sample, and set the length between the upper and lower clamps to 50mm before the test. Start stretching the sample at a tensile speed of 100mm / min until the sample just breaks. Record the distance between the two clamps as L1. Then the elongation of the sample = (L1-L0) / L0.
[0094] Table 1
[0095]
[0096] The high thermal conductivity adhesive layer was coated onto a scraper and the thickness was controlled to be 50 μm and the width to be 10 cm. After drying at 50 °C, it was peeled off to obtain a film. The volume resistivity and thermal conductivity of the film were tested, and the test results are shown in Table 2 below.
[0097] Table 2
[0098]
[0099]
[0100] in conclusion:
[0101] The data in Table 1 show that the copper-aluminum composite current collectors prepared in Examples 1 to 6 have good mechanical properties, which can effectively reduce the influence of internal stress in the battery and avoid wrinkles on the electrode sheets; they can decompose a large battery into sub-batteries, which is safer; and they also avoid the problem of the tabs being easily broken during stacking.
[0102] The data in Table 2 show that the high thermal conductivity adhesive coatings prepared in Examples 1-6 have good thermal conductivity and excellent electrical conductivity. Data from Example 1 and Comparative Example 1 indicate that the adhesive prepared in this invention has better thermal conductivity and electrical conductivity compared to conventional polyacrylic acid adhesives. Data from Example 2 and Comparative Example 2 show that modifying silicon carbide with polyethyleneimine effectively improves the compatibility between silicon carbide and the adhesive emulsion, which is beneficial for silicon carbide dispersion and thus improves the thermal conductivity of the adhesive layer. Data from Example 3 and Comparative Example 3 show that the addition time of components A and B needs to be carefully controlled when preparing the adhesive emulsion. Because Comparative Example 3 added components A and B simultaneously and reacted them with polyvinyl alcohol, the final adhesive layer had lower electrical conductivity than that of Example 3.
[0103] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0104] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high thermal conductivity distributed copper-aluminum composite current collector, characterized in that: The high thermal conductivity distributed copper-aluminum composite current collector includes a polymer film (3), a high thermal conductivity adhesive layer (2), a copper layer (1), and an aluminum layer (4); the high thermal conductivity adhesive layer (2) is attached to both sides of the polymer film (3); the copper layer (1) and the aluminum layer (4) are respectively bonded to the polymer film (3) through the high thermal conductivity adhesive layer (2); A method for preparing a high thermal conductivity adhesive coating liquid includes the following steps: S1: Prepare a polyvinyl alcohol solution; mix acrylamide, acrylic acid, and water and dissolve by ultrasonication to obtain material A; mix acrolein, acrylic acid, sodium 2-acrylamide-2-methylpropanesulfonate, ferric chloride, pyrrole, and water, and stir to react to obtain material B; S2: Under nitrogen atmosphere, add material A and potassium persulfate to polyvinyl alcohol solution, heat to 40-60℃, and react for 4-6 hours; add material B in 3-6 portions and continue the reaction for 6-8 hours; add ammonia water to adjust pH to 7-7.5 to obtain adhesive emulsion. S3: Mix modified silicon carbide powder, nano silver powder and binder emulsion, and stir for 30-60 minutes to obtain a high thermal conductivity adhesive coating liquid; In S3, the modified silicon carbide is prepared by dispersing silicon carbide powder in water, adding polyethyleneimine, stirring evenly, and then spray drying to obtain modified silicon carbide powder.
2. The high thermal conductivity distributed copper-aluminum composite current collector according to claim 1, characterized in that: The thickness of the high thermal conductivity distributed copper-aluminum composite current collector is 10-70 μm; the thickness of the copper layer (1) is 2-15 μm and the thickness of the aluminum layer (4) is 5-20 μm.
3. The high thermal conductivity distributed copper-aluminum composite current collector according to claim 1, characterized in that: The high thermal conductivity adhesive layer (2) is formed on the surface of the polymer film (3) by coating, pressure bonding, and aging of the high thermal conductivity adhesive layer coating liquid; the surface density of the high thermal conductivity adhesive layer coating liquid on one side is 1-20 g / m. 2 .
4. The high thermal conductivity distributed copper-aluminum composite current collector according to claim 1, characterized in that: In S1, the components of material A, by weight percentage, are 30-40% acrylamide, 10-20% acrylic acid, and 40-60% water; the components of material B, by weight percentage, are 10-15% acrolein, 35-45% acrylic acid, 5-10% sodium 2-acrylamide-2-methylpropanesulfonate, 10-15% ferric chloride, 2-3% pyrrole, and the remainder is water.
5. The high thermal conductivity distributed copper-aluminum composite current collector according to claim 1, characterized in that: In S2, the amounts of each component in the adhesive emulsion, by weight, are: 3.2–4.8 parts polyvinyl alcohol solution, 1.6–2.4 parts material A, 0.05–0.08 parts potassium persulfate, and 4.4–5.6 parts material B.
6. A method for preparing a high thermal conductivity distributed copper-aluminum composite current collector as described in any one of claims 1 to 5, characterized in that: Includes the following steps: Step 1: Mix modified silicon carbide powder, nano silver powder, and binder emulsion, stir to obtain a high thermal conductivity adhesive layer coating liquid, and coat it on the upper and lower surfaces of the polymer film to form a high thermal conductivity adhesive layer. Step 2: Take aluminum sheet and copper sheet, roll the aluminum sheet into aluminum foil; roll the copper sheet into copper foil; combine the aluminum foil and copper foil with a high thermal conductivity adhesive layer to form a copper layer and an aluminum layer, and then heat and age to obtain a high thermal conductivity distributed copper-aluminum composite current collector.
7. The method for preparing a high thermal conductivity distributed copper-aluminum composite current collector according to claim 6, characterized in that: Step 1 also includes unwinding the polymer film with an unwinding tension of 50–200 N; Step 2 also includes winding the high thermal conductivity distributed copper-aluminum composite current collector with a winding tension of 50–200 N.
8. The method for preparing a high thermal conductivity distributed copper-aluminum composite current collector according to claim 6, characterized in that: In step 2, the composite pressure is 0.5-1.5 MPa, the composite temperature is 30-40℃, the composite speed is 100-200 m / min, the aging temperature is 30-80℃, and the aging time is 5-30 s.
Citation Information
Patent Citations
Carbon-coated aluminum foil for lithium ion batteries
CN109935837A
Graphene composite silicon carbide dispersion slurry
CN115073180A